PELAKSANAAN PERKAWINAN DAN PROSES PERALIHAN TANAH KARENA WARISAN BAGI MASYARAKAT PADANG PARIAMAN DI PEKANBARU MENURUT HUKUM ADAT - Fadillah Purnama Sary (Jurnal Ekonomi, 2017)
From the research found out that parents and mamak’s role have changed proper to era transition and situation where the father’s role is very important therefore mamak’s role is not quite needed unless in undertaking the marriage where mamak in here is only playing a role to share the inheritance or if it intended, she will be asked the opinion. The undertaking marriage and inheritance of settlement abroad of Minangkabau People in Pekanbaru is still appropriate to acceptable custom in Padang Pariaman however not entirely custom carried out. System of inheritance applies the hereditary law of Minangkabau Custom that is Original Treasure of an heir namely High Heirloom inherited by Nephews/nieces of the heir, employment Treasure and collective treasure of the heir inherited by widow or daughters/sons of the heir. The implementation of the land handover carried out based on Civil Code where the process will assisted by Notary to land handover which caused by the heritage.